"دور التحول الرقمي في عمليات الحجز في تعزيز القدرة التنافسية للمطاعم والفنادق في مدينة طرابلس (Comprehensive Journal of Science, 2025)
This study aimed to measure the role of digital transformation in booking processes in enhancingthe competitiveness of restaurants and hotels in the city of Tripoli. To achieve this objective, adescriptive-analytical approach was adopted, and a questionnaire was used as a tool to collectdata from a random sample of 40 restaurants and hotels in the city.The study reached several important findings, most notably a strong, statistically significantpositive impact of digital transformation in booking processes on competitiveness. The results alsoshowed that all dimensions of digital transformation (ease of use, variety of options, speed ofcompletion, technical support, and implementation cost) significantly contribute to enhancingcompetitiveness, with "speed of booking completion" being the most influential dimension.Based on these findings, the study recommended that restaurants and hotels invest in fast anduser-friendly booking systems, adopt a multi-channel strategy, and provide effective technicalsupport to ensure a superior customer experience. It also recommended that relevant authoritiessupport and raise awareness about the importance of digitalization for developing the hospitalitysector in Tripoli.
Keywords: Digital Transformation, Booking Processes, Competitiveness, Restaurants, Hotels, Hospitality Sector, Tripoli, Libya